ANALISIS PENERAPAN CONTINUITY CUTTING BERDASARKAN ADEGAN DALAM MENDUKUNG UNSUR NARATIF PADA FILM CHEF - Alif Fauzan; Dwi Haryanto; Muhammad Zamroni (Program Studi Film dan Televisi Universitas Jember, 2019)
The Chef film is a Hollywood comedy drama, telling of Carl Casper's career as a chef. This study aims to analyze the editing aspects, especially the application of continuity cutting in supporting the narrative elements in Chef film using qualitative research methods, observation, documentation, library study and interactive model data analysis. The research found that some scenes that apply continuity cutting techniques such as 180º rule, shot/reverse shot, eyeline match, establishing/reestablishing shot, match on action, point of view cutting, crosscutting, Montage sequences, and cut-ins, can support the narrative element in the film Chef, because the storytelling on the movie Chef that is mutually sustainable can be delivered well to the audience.